The people living with HIV stigma survey UK 2015: HIV-related sexual rejection and other experiences of stigma and discrimination among gay and heterosexual men. Issue 9 (2nd September 2018) - Hibbert, M.; Crenna-Jennings, W.; Kirwan, P.; Benton, L.; Lut, I.; Okala, S.; Asboe, D.; Jeffries, J.; Kunda, C.; Mbewe, R.; Morris, S.; Morton, J.; et al.
ABSTRACT: We aim to understand the difference in stigma and discrimination, in particular sexual rejection, experienced between gay and heterosexual men living with HIV in the UK. The People Living with HIV StigmaSurvey UK 2015 recruited a convenience sample of persons with HIV through over 120 cross sector community organisations and 46 HIV clinics to complete an online survey. 1162 men completed the survey, 969 (83%) gay men and 193 (17%) heterosexual men, 92% were on antiretroviral therapy. Compared to heterosexual men, gay men were significantly more likely to report worrying about workplace treatment in relation to their HIV (21% vs. 11%), worrying about HIV-related sexual rejection (42% vs 21%), avoiding sex because of their HIV status (37% vs. 23%), and experiencing HIV-related sexual rejection (27% vs. 9%) in the past 12 months. In a multivariate logistic regression controlling for other sociodemographic factors, being gay was a predictor of reporting HIV-related sexual rejection in the past 12 months (aOR 2.17, CI 1.16, 4.02). Both gay and heterosexual men living with HIV experienced stigma and discrimination in the past 12 months, and this was higher for gay men in terms of HIV-related sexual rejection. Due to the high proportion of men reporting sexual rejection, greater awareness and education of the low risk of transmission of HIV among people on effective treatment is needed to reduce stigma and sexual prejudice towards people living with HIV.